Oracle BPEL Process Manager making SOA design easy. - Barbash, Brian (SOA webservices journal.)
Service oriented architecture (SOA), while its underpinnings have been around for years, has recently become one of the most talked about topics in the IT industry. The interest in SOAs is largely due to the emergence of Web services and their ability to expose business applications through well-defined interfaces in a platform-independent manner. While an SOA need not be built using Web services, it certainly presents an attractive option for a variety of environments.